A secure delegation scheme of large polynomial computation in multi–party cloud. (19th December 2014) - Guo, Shu; Xu, Haixia
Cloud computing is becoming widely used both in academia and industry and one of the most important applications is delegating computation. A computationally weak client delegates tasks to one or more workers in cloud, and this is called delegation computation. Delegation computation has high security requirements, and it needs to ensure that the information of the client would not be leaked and the computation will be computed correctly. What's more, the clients can verify the result after computation. This paper presents a delegation protocol and it allows the client to delegate a large polynomial to more than one worker while keeping privacy and correctness. In this paper, the workers make computations directly on the shares from the client, and keep the threshold unchanged. This protocol has these advantages: the protocol keeps privacy of the original input; the workers have no interaction with each other during the execution; the protocol keeps the threshold unchanged.